The Effect of Purchases on Comparison and Level of Service Quality in the E-Commerce Web Area (Case Study of Tokopedia and Bukalapak) - Muslimatul Husnah; Nia Andriani; Nurbaiti Nurbaiti (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The growth of technology that has entered all human life so that many people use it for something related to the economy. Technology and the advancement of the internet today really help everyone in meeting their needs. This includes trading transactions. E-commerce is growing with websites that have the capability to increase customer engagement and increase economic value. This incident is known as social commerce (s-commerce). Qualitative research that practices customer satisfaction styles with two e-commerce sites, namely Tokopedia. com and Bukalapak. com. This research also uses the procedures for collecting information sources in the form of documents. Transactions selling objects or services with computer network media connected to the internet are called e-commerce. The growth of e-commerce in Indonesia is very large due to the large population of Indonesia. Tokopedia and Bukalapak are popular e-commerce platforms in Indonesia in the form of a marketplace. The purpose of this study was to find a comparison of consumer satisfaction with the quality of the Tokopedia and Bukalapak web sites.